Pensions in Asia incentives, compliance and their role in retirement - Takayama Noriyuki (Tokyo Maruzen, 2005)
This volume is devoted to searching for better old age income security in Asia. With an introductory chapter, it contains reports on major East, Southeast and South Asian countries, including China , Chinese Taipei (Taiwan), Hong Kong, India, Japan, Sout
Consists of revised papers presented at the international conference held at Tokyo on 23rd & 24th Feb 2004
Keywords: Asia; Pensions